The Psychometric Properties of the Norwegian version of Beck Anxiety Inventory for youth and young adults (BAI) - Lisøy, Carina; Martinsen, Kristin (PsykTestBarn, 2023)
Description: The Beck Anxiety Inventory (BAI) is a self-report instrument for symptoms of anxiety developed by Beck, Epstein, Brown & Steer in 1988. The Norwegian version was translated by Tone Andersen in 2005 with the copyright belonging to NCS Pearson Inc. BAI has 21 items measured on a 4-point Likert-scale that sum to a total score. BAI is intended for ages 17 years or older. For respondents with normal reading comprehension, the instrument takes 5–10 minutes to complete. BAI results should be interpreted by medical doctors, clinical psychologists, or persons with an equivalent level of experience. Literature search: The search identified Scandinavian studies that reported psychometric properties or norm scores for BAI in samples of youth and young adults with a mean age below 26 years. Of 838 publications, 13 were included. Only one publication (a master’s thesis) was a psychometric study. Psychometrics: One study found that participants with anxiety diagnoses scored higher on the BAI than participants with depression. Criterion-validity was examined in one publication, which found low diagnostic accuracy. Convergent validity, assessed by correlation coefficients between BAI and other measures of anxiety, varied from “insufficient” to “excellent”. The factor structure of BAI was examined in one publication that was not peer reviewed. Overall, the factor structure of BAI in Scandinavia, and internationally, is unclear. Internal consistency was reported in 11 publications, which all found high internal consistency for BAI. Good to excellent test-retest reliability was found in three publications. We did not find BAI norm scores for Scandinavian samples, information about sensitivity to change, or measurement invariance in the included publications. Conclusion: The psychometric properties of BAI are not well documented in Scandinavian youth or young adult samples. We thus recommend that the instrument is used with caution for youth and young adults until psychometric properties of Scandinavian versions have been documented for the BAI.